(untitled) (Journal of Parents and Teachers, 2025)
The article discusses the TV series *The Flintstones*, where a woman’s life is reduced to staying and living in the cave to fully care for the children, while men are the ones who go out to hunt and work. The series reflects on modern society, stating that there is still much progress to be made in addressing these differences.